e-Proceedings book: International Conference On Sustainability Engineering Education (ICSEE2023) - Putra Jaya, Ramadhansyah (Association for Researcher of Skills and Vocational Training (ARSVOT), 2022)
The International Conference on Sustainability Engineering Education (ICSEE 2023) was held in a hybrid format at Corus Hotel Kuala Lumpur. ICSEE 2023 also received participation from various countries, including Malaysia, Indonesia, China, Oman, Iraq, and Japan, with a total of 36 presenters.